A geographic look at the Grapiúna identity: the identity of terras do sem fim of Jorge Amado - Santos, Rita de Cássia Evangelista dos (2018)
This article searches in the novel Terras do Sem Fim elements that, according to Jorge Amado, are typical features of the grapiúna identity, the cocoa region of Bahia. By narrating the disputes over lands for the planting of cocoa, in the south region of Bahia, in the late nineteenth and early twentieth century, Jorge Amado provides us with many characteristics about this region where as a result of the intense migratory process, different social subjects with their customs, beliefs, experiences, habits which resulted in a cultural region with its own identity and having cocoa as the great symbol. The bibliographical research was used as methodology, based it on texts written by important authors who have studied the theme of identity. The book "O que faz ser nordestino" by Maura Penna (1992) was used as a methodological resource, and the hypotheses that the author points out about the characteristics of the Northeast people were correlated with the ideas of the novel in which Jorge Amado presents